2016
DOI: 10.1093/gerona/glw219
|View full text |Cite
|
Sign up to set email alerts
|

Beet Root Juice: An Ergogenic Aid for Exercise and the Aging Brain

Abstract: Older adults who exercised and consumed BRJ demonstrated greater consistency within the motor community and fewer secondary connections with the insular cortex compared with those who exercised without BRJ. The exercise + BRJ group had brain networks that more closely resembled those of younger adults, showing the potential enhanced neuroplasticity conferred by combining exercise and BRJ consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Differences in the results might be due to the small sizes of the investigated groups (8–64 participants) [ 127 , 128 , 129 , 130 ]. In 2022, it was concluded that beetroot consumption is not important in this aspect [ 131 ].…”
Section: Influence Of Root Vegetables On Healthmentioning
confidence: 99%
“…Differences in the results might be due to the small sizes of the investigated groups (8–64 participants) [ 127 , 128 , 129 , 130 ]. In 2022, it was concluded that beetroot consumption is not important in this aspect [ 131 ].…”
Section: Influence Of Root Vegetables On Healthmentioning
confidence: 99%
“…In addition, the consistency of the SMC community increased after the dance intervention. Increased community consistency within this region has been shown to occur after exercise in older adults and is tied to positive outcomes (Petrie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of potential interventions 236 including ketones, 169 MUFA, SFA, n-3 and n-6 PUFAs, 283 B vitamins, vitamin E, carotenoid, carotene and lycopene, 283 resveratrol, 284,285 cholesterol related lipids, 286 beetroot juice 287 225 Isoprostanes formed by free-radical-mediated peroxidation of PUFAs in response to inflammation are AD biomarkers, 226 though studies associate them with other dementias. 227 Novel metabolomic studies can reveal several potential AD biomarkers in urine, including DCAs and lysophospholipids.…”
Section: Functional Connectivity Fmrimentioning
confidence: 99%